Musa pest fact sheet on the banana weevil Cosmopolites sordidus - Gold, Cliford S.; Messiaen, S. (2000)
This fact sheet provides information about the banana weevil Cosmopolites sordidus, a pest of bananas (Musa spp.), plantains and ensete. It includes details about its biology, life cycle, symptoms, distribution, control and research needs, and photos of the pest and symptoms.